INVESTIGATING LEARNERS’ PERCEPTION OF ENGLISH ONLINE LEARNING IN BANYUWANGI SECONDARY SCHOOL - St. Shabibatul Rohmah; Umi Resita Kusmawati; Totok Hari Prasetiyo; Mochamad Ardi Setyawan; Mahfud (SOSIOEDUKASI, 2023)
This research aims to discover and describe some of the learners' perceptions of English online learning. This research’s approach or design is qualitative, carried out in two stages. All the eleventh grade high school participants were given an online questionnaire in the first stage. Then in the second stage, several participants were interviewed to clarify the research result. Based on the research result, students had several perceptions about English online learning. The first perception, students stated that the learning environment between English online learning and face to face learning is so different. They also added that the interaction in English online learning did not go well. The third perception, students said that the assignments given during English online learning were so many that they were less than optimal in doing assignments. Lastly, students revealed that when English online learning, they prefer to deliver material using videos and tend not to read the material. In brief, this research discover several students’ perception during their online learning, they are the differentiation of the learning environment, the interaction in English online learning didn’t go well, too many assignments given in online learning makes students less optimal, and students prefer to deliver material using videos.